1991
DOI: 10.1007/bf02549731
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in young males with hypotestosteronaemia and oligospermia prior to, during, and after treatment

Abstract: Relationships between plasma testosterone levels and selected parameters of lipid metabolism were studied in a group of young sterile males prior to, during, and after hormone therapy. Initial hypertriacylglycerolaemia and decreased concentrations of HDL cholesterol returned to normal values after 30 days of methyltestosterone administration. LDL cholesterol concentrations decreased significantly as did plasma apolipoprotein B levels. These changes persisted also one month after cessation of treatment. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The reason for statin therapy was secondary prevention for vascular disease in most cases. Despite the presence of vascular disease, the dyslipidemia in these patients may reflect the underlying androgen status, because there are reports of dyslipidemia associated with hypogonadism (29,30). However, the raised body mass index and high prevalence of type 2 diabetes (n ϭ 9) are also likely to contribute.…”
Section: Discussionmentioning
confidence: 94%
“…The reason for statin therapy was secondary prevention for vascular disease in most cases. Despite the presence of vascular disease, the dyslipidemia in these patients may reflect the underlying androgen status, because there are reports of dyslipidemia associated with hypogonadism (29,30). However, the raised body mass index and high prevalence of type 2 diabetes (n ϭ 9) are also likely to contribute.…”
Section: Discussionmentioning
confidence: 94%
“…For example, women with polycystic ovary syndrome have increased cardiovascular disease risk factors compared with controls, including increased total cholesterol (TC), LDL-C, and triglyceride (TG) levels, as well as lower HDL-C levels (63,64). Additionally, men with hypotestosteronemia are reported to have depressed HDL-C levels compared with controls (65,66), and high levels of TC and TG are associated with poor semen quality and azoospermia (67). In one report, a dyslipidemia incidence of 65% was found in a set of 106 men with reproductive concerns (68).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, low serum testosterone levels can predict the development of lipometabolic disturbance (Guay & Jacobson, ; Rodriguez et al ., ). Fortunately, TST was found to improve the lipid profile of men with AD, as reported by Hromadová in 1991 (Hromadová et al ., ). Meanwhile, several studies have found that TST does not significantly change serum lipid concentration (Heufelder et al ., ; Hellstrom et al ., ).…”
Section: Discussionmentioning
confidence: 97%